Coordination in place of integration? Economic governance in a non-federal EU - Renaud Thillaye (WWWforEurope, 2013)
The most commonly held opinion about the eurozone crisis is that it should lead to greater EU integration. Yet despite all the talk about fundamental design flaws and the need for a federal `leap forward', EU governments and citizens are not ready to pool further sovereignty and resources as a way to strengthen the common currency and to improve the EU's delivering capacity. Blueprints and roadmaps for completing the Economic and Monetary Union have been dealt with contempt by national leaders. As a result, more attention ought to be focused on how the imbalances threatening the EU's cohesion and stability could be addressed within the existing boundaries of EU treaties. Improving the current set-up of policy coordination should be the priority of the next few years. This policy paper suggests ways to improve the institutions and scope of policy coordination in the EU. In terms of substance, the experience accumulated before and after the crisis has shown that a narrow approach in terms of fiscal and macroeconomic discipline is not enough. If EU member states do not want markets to impose adjustments in their own terms, they must embrace a broader approach to convergence and improve the conditions in which they adjust to each other. Wage and social developments should be included in EU supervision frameworks. As regards institutions, more reflection should be devoted to the innovations that would increase the impact of mutual commitments. This paper analyses the increasing contractual approach to EU governance, and argues that a stronger sense of reciprocity could arise from ad hoc cooperations on a smaller scale for the euro area and voluntary countries. One should nevertheless be clear about the limits of what coordination can achieve. Greater ambition in terms of EU cohesion and democratic legitimacy would require a more substantial rethink of EU policy-making in the long term.
Keywords: E02; 330; EU integration; European economic policy; European governance; European Monetary Union; good governance; multi-level governance; policy options; political economy of policy reform